Success factors for peer-to-peer lending for SMEs: Evidence from Indonesia - Mohammad Yunies Edward; Eko Nur Fuad; Hadi Ismanto; Apriani Dorkas Rambu Atahau; Robiyanto (Investment Management & Financial Innovations, 2023)
Sharia fintech lending grew up at the teenage stage and has successfully taken a strategic place in the Indonesian loan market. Adopting the economics of information and signaling theory, this paper investigates the probability of successful crowdfunding. Using cross-section data, this study analyzes 1,153 funded projects on Ammana.id platform, a well-known Indonesia’s sharia P2P lending. This study runs OLS regressions to examine the effect of loan information (ranking, estimated profit shares, and financing duration) on the amount of crowded funding. This finding support both theories, that the information about the loan is a signal in determining the success of project funding. Ranking and duration of financing significantly affect the success of the P2P sharia lending platform, nevertheless profit share estimation is not significant. Loans that operated in short, tend to raise more funding, and vice versa. Loan ranking can provide the lender with instant information about the borrowers’ condition. Lenders tend to avoid low rankings loans due to the potential failure of loan payments. This study also found a surprising result that the coefficient of profit sharing is positive for Islamic funding but insignificant. This result shows that material gain is not the main issue for investors, but the elements of trust and justice are nobler according to Islamic beliefs. This study proves that loan information as a low-cost signal can be used by investors to make the best decision and reduce adverse selection problems. The findings support the strategic growth of Islamic platforms to build a sustainable Islamic investment and maintain financial stability. Acknowledgments Appreciation is given to the General Directorate of Higher Education, Research and Technology, Ministry of Education, Culture, Research and Technology, and the Institute for Research and Community Service of Universitas Islam Nahdlatul Ulama (Unisnu) Jepara, Indonesia.